The Communication Effectiveness of Garden Circle Organization in Improving the Performance of Nusantara Plantation Employees, PTPN II Bandar Kliffa Plantations and PTPN III Sei Putih Plantations in North Sumatra, (Islamic Perspective Study) - Selamat Riadi; Syukur Kholil; Yusnadi Yusnadi (Budapest International Research and Critics University, 2020)
This study aims to analyze: (1) Clarity of information in implementing the garden circle communication in improving the performance employees, (2) Situation of garden circle communication environment is carried out in improving the performance employees. (3) Communicator manners communicate with employees in improving the performance employees, and (4) Implementation of Islamic communication principles in the garden circle in improving the performance employees. This research uses a qualitative approach with descriptive methods. Research subjects include managers, security personnel, assistants, foremen and implementing employees at Nusantara II and III Plantations on garden circle activities. Data collection techniques through interviews, observation and documentation. Data were analyzed using the Miles and Hubermen model technique. The results showed that the circle of the garden provides clarity of information, creates a conducive communication environment situation and shows manners in communication, and uses the principles of Islamic communication in the implementation of the garden circle. Thus the communication around the garden is quite effective in improving the performance of employees of Nusantara II Bandar Kliffa and PTPN III Sei Putih Plantations.